A Bibliometric History of the Journal of Promotion Management (1992–2019). Issue 1 (2nd January 2020) - Kumar, Satish; Spais, George S.; Kumar, Divesh; Sureka, Riya
Abstract: The Journal of Promotion Management: Innovations in Planning and Applied Research (JPM) has been serving as a platform for research in promotion management since 1992. The major objective of this study is to provide a lifetime overview of the academic structure of the JPM publications through bibliometric analysis. We extracted bibliographic data of the journal from the Scopus database and we highlighted significant trends and themes of the journal employing different bibliometric tools. Significant findings indicate that the JPM has grown both in terms of productivity and influence. Authors affiliated to the USA are shown to be the major contributors to the journal. Bibliographic coupling of JPM documents showed that the major research themes published in the journal include online marketing, celebrity endorsement, consumer skepticism, social media, sales promotion, price promotion, green marketing, product placement, brand placement, relationship management and crisis management.